Prognostic efficacy of circulating asymmetric dimethylarginine in patients with peripheral arterial disease: A meta-analysis of prospective cohort studies. (June 2018) - Chu, Renzhu; Yu, Dawei; Chu, Junyi; Lin, Mingqiang; Yu, Hongbo
Abstract: Background: Asymmetric dimethylarginine is suggested to be a marker of poor prognosis in patients with atherosclerosis. However, the predictive role of circulating asymmetric dimethylarginine for clinical outcome in patients with peripheral arterial disease has not been determined. Aims: To quantitatively assess the predictive value of circulating asymmetric dimethylarginine for clinical outcome in patients with peripheral arterial disease in a meta-analysis of prospective cohort studies. Methods: Relevant studies were identified by systematically searching of PubMed and Embase databases. A random-effect model was used to synthesize the results. Sensitivity analyses by omitting one study at a time were performed to evaluate the robustness of the results. Results: Six studies with 2535 peripheral arterial disease patients were included. Patients with higher circulating asymmetric dimethylarginine at baseline were associated with higher risk of all-cause mortality (adjusted hazard ratio: 1.63, 95% confidence interval: 1.28–2.06, I 2  = 16%), and major adverse cardiovascular events (adjusted hazard ratio: 2.01, 95% confidence interval: 1.08–3.73, I 2  = 78%) as compared with those with lower circulating asymmetric dimethylarginine at baseline. Specifically, every increment of 0.1 µmol/l of asymmetric dimethylarginine was associated with 18% (adjusted hazard ratio: 1.18, 95% confidence interval: 1.06–1.31) increased risk for all-cause mortality and 14% (adjusted hazard ratio: 1.14, 95% confidence interval: 1.04–1.25) increased risk for major adverse cardiovascular disease. Sensitivity analyses by omitting one study at a time did not significantly change the results. Conclusion: Higher circulating asymmetric dimethylarginine at baseline may be associated with higher incidence of cardiovascular events and mortality in patients with peripheral arterial disease.